A wide temperature solid-state Li–S battery enabled by a plasmon-enhanced copper–silicon nanowire photothermal current collector. Issue 42 (12th October 2022) - Song, Xiaoying; Wang, Min; Wang, Sheng; Cheng, Zhu; Zhang, Ting; Zhu, Ting; Song, Hucheng; Yu, Linwei; Xu, Jun; Chen, Kunji
Abstract : A wide temperature solid-state Li–S battery that can efficiently harvest omnidirectional solar energy and convert it into heat via a hierarchical copper–silicon nanowire photothermal current collector. Abstract : Solid-sate lithium-ion batteries (LIBs), especially lithium–sulfur (Li–S) batteries, are one of the most promising candidates for developing high energy density and high safety energy storage devices. However, current solid-state Li–S batteries can only work well at a relatively high operating temperature (>50 °C) due to the poor Li-ion transfer kinetics at electrodes/electrolyte and their interfaces which make these batteries lose most of their capacity and power as the temperature falls below room temperature. Here, we report an extra-wide operating temperature solid-state Li–S battery that can efficiently harvest omnidirectional solar energy and convert it into heat via a hierarchical copper–silicon nanowire photothermal current collector. Such a current collector enables broad solar spectrum absorption (>93%) with a wide incident angle (0 degree to 70 degree) and efficient conversion of light-to-heat, improving charge storage and transmission at electrodes/electrolyte and their interfaces even at low operating temperatures. As a result, the battery demonstrates low impedance (∼10 2 Ω cm 2 ), a high discharge capacity of ∼900 mA h g −1 at room temperature, ∼960 mA h g −1 at 60 °C and a discharge capacity of ∼260 mA h g −1 at −60 °C. Such a design provides an effective solution for all-solid-state LIBs operating at a low temperature.